PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA CADDIE PADANG GOLF HALIM - Fitriyah Rahmawati; Leonardo Indra Vitaharsa (CV. Adiba Aisha Amira, 2024)
The aim of this research is to examine the influence of leadership, organizational culture and work discipline on the performance of Padang Golf Halim caddies. This research method uses accidental sampling. The purpose of this technique is to take samples by chance or people the author meets at that time. The sample for this study consisted of one hundred Padang Golf Halim caddies. Data was obtained using a questionnaire and processed using SPSS 20 software. The results of this research are shown by the results of the F test where sig 0.000 < 0.05, which means that these variables together have a significant influence on employee performance variables. The aim of this research is to examine the influence of leadership, organizational culture and work discipline on the performance of Padang Golf Halim caddies. This research method uses accidental sampling. The purpose of this technique is to take samples by chance or people the author meets at that time. The sample for this study consisted of one hundred Padang Golf Halim caddies. Data was obtained using a questionnaire and processed using SPSS 20 software. The results of this research are shown by the results of the F test where sig 0.000 < 0.05, which means that these variables together have a significant influence on employee performance variables.